Percutaneous Valve Replacement: Where Do We Stand? Where Are We Going? - Roach, Emir Charles; Gezgen, Gamze; Gezgen, Baki (Drunpp-Sarajevo, Bolnicka Bb, Sarajevo, 71000, Bosnia & Herceg, 2010)
Background: Percutaneous valve replacement is a relatively new treatment modality that is rapidly growing in application. Aim&Objectives: Percutaneous treatment of valve diseases has been an alternative to open surgery since the early 1980's. In patients with mitral and aortic stenosis, use of percutaneous catheter-based techniques as balloon valvuloplasty has been a good therapeutic option. Later on, percutaneous aortic valve replacement was demonstrated in the 1990s in vitro, followed by successful in vivo applications. Although these techniques have difficulties such as paravalvular leakage difficulty in deployment; migration of valved stent; percutaneous valve replacement is currently one of the most researched and actively debated subjects in interventional cardiology. In this study we are aiming to review the current state and evaluate the pros and cons of this new treatment modality. Methods/Study Design: We enumerated the pros and cons from different perspectives, referenced and discussed them from articles that were obtained through Pubmed. Results and Findings: Percutaneous valve replacement procedures offer substantial advantages to patients. The reducing of surgical risks, the fact that the procedures are less invasive in comparison to open heart surgery, and that rehabilitation times are shorter are positive aspects [2]. However, there are complications such as paravalvular leakage difficulty in deployment; migration of valved stent, that needed to be taken into consideration and the selection of patients for the procedure needs improvement. Study Limitations: Percutaneous valve replacement is a relatively new treatment modality, few publications exist for consideration. Conclusion: With 12 different kinds of valves available for use, and improvement in patient selection, we expect to see an increase in percutaneous valve replacements worldwide.
Keywords: Percutaneous Valve Replacement; Mitral Aortic; correct mitral-insufficiency; to-edge technique; aortic-valve; pulmonary valve; transcatheter implantation; clinical-experience; natural-history; repair; regurgitation; stenosis; Perkütan Vana Değişimi; mitral aort; Doğru mitral-yetersizliği; pulmoner kapak; transkateter implantasyonu; Klinik-deneyim; doğal tarih; onarım; yetersizlik; darlık